Ecosystem Services Come To Town Greening Cities by Working with Nature - Grant, Gary (Wiley, 2012)
Gary Grant is a Chartered Environmentalist, Member of the Institute of Ecology and Environmental Management, an Academician at the Academy of Urbanism, Member of the All Party Parliamentary Committee on Biodiversity, thesis supervisor at the Bartlett Faculty of the Built Environment, University College London, Chair of the Judges of the Integrated Habitats Design Competition and Director of the Green Roof Consultancy Ltd. As director of EDAW and then AECOM Design + Planning and now independent, he has worked on large scale planning projects including the London 2012 Olympic Park, the Bedford Valley River Park, the Whitehill-Bordon Eco Town, Education City, Qatar and Saadiyat Island, Abu Dhabi